A history of Syria in one hundred sites - Kanjou, Youssef,; Tsuneki, Akira, 1954- (Archaeopress Archaeology, 2016)
This volume presents the long history of Syria through a journey of the most important and recently-excavated archaeological sites. The sites cover over 1.8 million years and all regions in Syria; 110 academics have contributed information on 103 excavations for this book.